Frequency Of Hyponatremia In Children Admitted To The Pediatric Intensive Care Unit In A Tertiary-Care Hospital: A Cross-Sectional Study - Ammar Yasir Khan; Arooba Idris; Asad Shabbir; Sobia Rashid; Asad Iqbal Danish; Syeda Mamoona Qudrat (Journal of Rawalpindi Medical College)
Objective: Hyponatremia is relatively common in children with acute diarrhoea, occurring in around 10-15% of cases. This study aimed to determine the prevalence of hyponatremia in children with acute diarrhoea.